2006
DOI: 10.1140/epja/i2006-08-025-6
|View full text |Cite
|
Sign up to set email alerts
|

Pygmy dipole strength close to particle-separation energies --The case of the Mo isotopes

Abstract: Abstract. The distribution of electromagnetic dipole strength in 92, 98, 100 Mo has been investigated by photon scattering using bremsstrahlung from the new ELBE facility. The experimental data for wellseparated nuclear resonances indicate a transition from a regular to a chaotic behaviour above 4 MeV of excitation energy. As the strength distributions follow a Porter-Thomas distribution much of the dipole strength is found in weak and in unresolved resonances appearing as fluctuating cross section. An analys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
47
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 28 publications
6
47
2
Order By: Relevance
“…The experimental data points show two enhancements at around 9 MeV and 10.5 MeV, in good agreement with our results, which predict a K π = 1 − mode peak at 8.9 MeV and a double K π = 0 − mode peak at 10.5 MeV. In addition to these, Figure 7.10 shows another theoretical K π = 0 − peak at 7.4 MeV, which can be linked to the 7 MeV enhancement found in the results from reference [134]. In that same study, another peak was found at 6.5 MeV with strong dipole strength.…”
supporting
confidence: 91%
See 4 more Smart Citations
“…The experimental data points show two enhancements at around 9 MeV and 10.5 MeV, in good agreement with our results, which predict a K π = 1 − mode peak at 8.9 MeV and a double K π = 0 − mode peak at 10.5 MeV. In addition to these, Figure 7.10 shows another theoretical K π = 0 − peak at 7.4 MeV, which can be linked to the 7 MeV enhancement found in the results from reference [134]. In that same study, another peak was found at 6.5 MeV with strong dipole strength.…”
supporting
confidence: 91%
“…The red and blue curves correspond to the K π = 0 − and K π = 1 − excitation modes, respectively. The experimental data was taken from references [14,134]. Interestingly enough, at a first glance to Figure 7.9 the NL3 parameter set seems to perform better, in agreement with the Lorentzian fits parameters.…”
Section: Mosupporting
confidence: 58%
See 3 more Smart Citations